STRATEGI EFEKTIF DALAM MENINGKATKAN PENJUALAN MELALUI SOSIAL MEDIA DI ERA DIGITAL - Afriani Afriani; Yuni Fatma Sari; Siti Hansyah Dewi Zai; Fanny Himla Rizqya Pasaribu; Nurbaiti Nurbaiti (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
This study examines effective strategies in increasing sales through social media in the digital era. With the increasing use of social media platforms, businesses need to adopt innovative approaches to reach a wider audience. This study uses qualitative methods to explore various social marketing techniques that can increase sales engagement and conversion. The results show that building credibility, quality content, active interaction, and collaboration with influencers are key factors in achieving sales goals. The development of digital technology has changed the way companies market their products and services. Social media has become an important platform in reaching consumers more closely, and has the potential to increase sales significantly. This article discusses effective social media marketing strategies in increasing sales such as developing interesting content, utilizing influencers, using paid advertising and fast customer interaction and service that are often encountered in social media marketing strategies and how to utilize data analytics to support marketing decisions.